A Method of Multi-channel Data Acquisition with Adjustable Sampling Rate - Su Shujing; Lei Jiansheng (Institute of Advanced Engineering and Science, 2013)
Sampling rate of current signal acquisition systems are singular. Aiming at this shortcoming, a method of multi-channel data acquisition(DAQ) with adjustable sampling rate is presented. The method realizes the cut-off frequency of anti-aliasing filter controlled by program with the help of switched-capacitor; by independently pulsing sampling signal of different ADCs, 16-channel sampling rate are adjustable within the range 50ksps, 25ksps, 10ksps, 5ksps, 1ksps. Theoretical analysis and experimental verification pointing at the proposed method are implemented: theoretical analysis shows that parameters of the filter meet the design requirements; experimental results show that cut-off frequency of the anti-aliasing filter matches variable sampling rate very well; choosing appropriate sampling rate according to the characteristics of the measured signal not only can well restore the measured signal, but also prevents system resources from waste. This method can meet needs of testing various signals with different frequency at the same time. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3283